Clogging-Free Irreversible Bonding of Polycarbonate Membranes to Glass Microfluidic Devices. Issue 5 (1st January 2017) - Wang, Chenxi; Gao, Xiaofang; Mawatari, Kazuma; Kitamori, Takehiko
Abstract : An irreversible bonding method for bonding porous polycarbonate membranes to glass microfluidic devices is demonstrated. The membrane surfaces were modified with an ammonia solution that contained amino hydrophilic groups. Additionally, the glass substrates were terminated with hydroxyl groups after exposure to an oxygen plasma. Based on the dehydration reaction, reliable bonding between the glass and the porous membrane was achieved at 110°C and was verified by the fluidic leakage tests for burst pressure (>500 kPa) and long-term durability (∼5 days). In particular, chemical modification by small ammonia molecules allowed bonding of the porous membranes without clogging to the pores. Therefore, this method has great potential for use in nanofluidic channels integrated with nanoporous membranes. Moreover, a simple disassembly strategy for the sandwich-structured microfluidic devices was proposed and realized for the reuse and recycling of glass substrates with microchannels in the event that the membrane morphology changes after long-term use.